2010
DOI: 10.3109/02652040903010638
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, characterization and testing of tetracaine hydrochloride-loaded albumin-chitosan microparticles for ocular drug delivery

Abstract: Most ocular surgical procedures take approximately 60 min to complete, the anaesthetic property of the safest drug, tetracaine, is initiated in a few minutes and lasts approximately 10-15 min. The purpose of the present study was to develop an ocular tetracaine formulation which can produce an immediate onset of action and/or longer duration of action during the entire surgical procedure. Tetracaine-loaded microparticle formulation was prepared by the method of spray-drying and characterized in terms of size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…This difference can be attributed to difference in solubility of chitosans [108]. Similar results were reported in other studies [109][110][111][112].…”
Section: Nasal Delivery Systemssupporting
confidence: 86%
“…This difference can be attributed to difference in solubility of chitosans [108]. Similar results were reported in other studies [109][110][111][112].…”
Section: Nasal Delivery Systemssupporting
confidence: 86%
“…Finally, the particles loaded with drugs obtained by spray-drying could be administered by different routes such as oral [127][128][129][130][131][132], pulmonary [12,23,82,133,134), ophthalmic [93,111,135], parenteral [22,38,136], nasal [60,120,121,137], and vaginal [138], stressing its great In vitro tests showed that their mucoadhesion was 2-fold higher than that of a hydroxyethylcellulose gel formulation [138].…”
Section: Different Routes Of Administration Of Drug-loaded Polymeric mentioning
confidence: 99%
“…into particles could protect the cargo against harsh conditions such as chemical and enzymatic degradation[28,93]. For example, Seremeta et al encapsulated the anti-HIV didanosine within poly(epsilon-caprolactone) (PCL) MPs both by suspension and simple emulsion followed for spray-drying to avoid its fast gastric degradation that leads to low oral bioavailability (20-40%)[51].…”
mentioning
confidence: 99%
“…In most cases such microspheres are made in the absence of cells, for use as drug or growth factor delivery vehicles (Addo et al, 2010; Solorio et al, 2010) or as microcarrier substrates for subsequent attachment of cells to the surface (Gorodetsky et al, 2004; Natesan et al, 2010). In some cases, cells have been entrapped directly inside the microbeads.…”
Section: Introductionmentioning
confidence: 99%